Bidirectional associations between psychosocial well-being and adherence to healthy dietary guidelines in European children: prospective findings from the IDEFICS study - Louise Arvidsson; Gabriele Eiben; Monica Hunsberger; Ilse De Bourdeaudhuij; Denes Molnar; Hannah Jilani; Barbara Thumann; Toomas Veidebaum; Paola Russo; Michael Tornatitis; Alba M. Santaliestra-Pasías; Valeria Pala; et al. (BMC, 2017)
Abstract Background In children the relationship between a healthy diet and psychosocial well-being has not been fully explored and the existing evidence is inconsistent. This study investigates the chronology of the association between children's adherence to healthy dietary guidelines and their well-being, with special attention to the influence of weight status on the association. Methods Seven thousand six hundred seventy five children 2 to 9 years old from the eight-country cohort study IDEFICS were investigated. They were first examined between September 2007 and June 2008 and re-examined again 2 years later. Psychosocial well-being was measured using self-esteem and parent relations questions from the KINDL® and emotional and peer problems from the Strengths and Difficulties Questionnaire. A Healthy Dietary Adherence Score (HDAS) was calculated from a 43-item food frequency questionnaire as a measure of the degree to which children's dietary intake follows nutrition guidelines. The analysis employed multilevel logistic regression (country as random effect) with bidirectional modeling of dichotomous dietary and well-being variables as both exposures and outcomes while controlling for respective baseline values. Results A higher HDAS at baseline was associated with better self-esteem (OR 1.2, 95% CI 1.0;1.4) and fewer emotional and peer problems (OR 1.2, 95% CI 1.1;1.3 and OR 1.3, 95% CI 1.2;1.4) 2 years later. For the reversed direction, better self-esteem was associated with higher HDAS 2 years later (OR 1.1 95% CI 1.0;1.29). The analysis stratified by weight status revealed that the associations between higher HDAS at baseline and better well-being at follow-up were similar in both normal weight and overweight children. Conclusion Present findings suggest a bidirectional relation between diet quality and self-esteem. Additionally, higher adherence to healthy dietary guidelines at baseline was associated with fewer emotional and peer problems at follow-up, independent of children's weight status.